Chapter 14: Clinical Decision Making (Pharmacy Essentials: A Compact Guide for Students and Practitioners, 2025)
AuthorDr. Amit Kumar, Associate Professor, Department of Pharmacy Practice, Amity Institute of Pharmacy, Amity University, Lucknow, IndiaAbstractClinical decision making applies systematic cognitive processes to pharmaceutical care, integrating evidence evaluation with patient-specific factors to optimize therapeutic outcomes. Evidence-based practice combines research evaluation, clinical expertise, and patient preferences through structured approaches identifying answerable clinical questions, efficiently searching information sources, critically appraising literature quality, applying findings to specific patients, and evaluating outcomes, with hierarchies rating evidence from meta-analyses and randomized controlled trials to case reports and expert opinion. Clinical guidelines implementation translates consensus recommendations into practical application through identification of relevant guidelines, assessment of evidence quality and applicability, adaptation to local resources and patient populations, implementation strategies addressing barriers, and outcome monitoring evaluating adherence and clinical impact. Patient case analysis employs structured frameworks systematically evaluating subjective and objective information, including comprehensive medication reviews identifying actual and potential drug-related problems, with particular attention to indication appropriateness, effectiveness assessment, safety evaluation, and adherence factors across acute and chronic conditions. Therapeutic problem solving applies clinical reasoning models to complex medication challenges through clear problem definition, generation of multiple intervention options, systematic evaluation of alternatives against therapeutic goals, implementation of selected interventions, and ongoing monitoring with adjustment based on response, incorporating both analytical and intuitive processes while considering patient-specific contexts, preferences, and clinical variables. Decision-making principles enable pharmacists to translate theoretical knowledge into practical interventions that address individual patient needs while incorporating best available evidence and professional judgment.Keywords: Clinical Reasoning; Literature Evaluation; Problem Identification; Intervention Selection; Evidence-Based PracticeVIEW PDF